Studi Eksplorasi Perkembangan Bahan Ajar Pendidikan Pancasila untuk Perguruan Tinggi Pada Era Paska Reformasi (Studi Kasus di Yogyakarta) - Hastangka (Civic-Culture : Jurnal Ilmu Pendidikan PKN dan Sosial Budaya, 2019)
The objective of this study is to map and to find out the development and change of thecontents of the teaching materials in Pancasila Education for higher education in thepost-reform era. This study explores how the development and changes undergo in thecontent of it which rarely become a concern and study from academics and Pancasilaresearchers. In particular, this study explores the development and changes of theteaching materials in Pancasila Education for universities through case studies on booksor the other teaching materials that have been published or circulated in many bookshopsin Yogyakarta region. The methods used in this study are literature review andobservation of the five well-known public bookshops in Yogyakarta which have becomepublic reference, such as Gramedia, Kanisius, Toga Mas, Social Agency, and ShoppingCenter located in Malioboro. The results of this study indicate that the sources andcontents of the teaching materials in Pancasila Education have various contents andapproaches which depend on the author's perspectives. This study finds that thebookshops in Yogyakarta provide the teaching materials of Pancasila Education fromvarious authors and publishers. The teaching and learning of Pancasila Education inhigher education becomes a lot easier since there are many variants of teachingmaterials. The conclusion of this study shows that the teaching materials for PancasilaEducation for Higher Education in the post-reform era has undergone rapid developmentand changes.